Pinay on the prairies Filipino women and transnational identities - Bonifacio, Glenda Tibe 1963- (UBC Press, 2013)
For many Filipinos, one word – kumusta, how are you – is all it takes to forge a connection with a stranger anywhere in the world. In Canada’s prairie provinces, this connection has inspired community building and created both national and transnational identities for the women who identify as pinay. This book is the first to look beyond traditional metropolitan hubs of settlement to explore the migration of Filipino women in Alberta, Manitoba, and Saskatchewan. Based on interviews with first-generation immigrant Filipino women and temporary foreign workers, Pinay on the Prairies is a revealing study of identity and community in Canada and an exploration of feminism, transnational identities, migration, and diaspora in a global era.--Provided by publisher.